ANALISIS PEMANFAATAN WHATSAPP GROUP SEBAGAI MEDIA BELAJAR DARING DI KELAS V SDN 002 SAMARINDA UTARA - Siska Oktaviani (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This study aims to describe information regarding the use of WhatsApp Groups as an online learning medium during the Covid-19 pandemic. This research was conducted in class V of SDN 002 North Samarinda, Samarinda City in the odd semester from September to December 2021. This research is a qualitative descriptive. The resource persons in this study were three class teachers and 6 students. Collecting data in this study carried out various techniques, namely observation, interviews and documentation. Activities in analyzing data in this study were carried out through data collection, data reduction, data presentation and drawing conclusions. To test the validity of the data in this study using triangulation techniques. The results of the study obtained information that WhatsApp became the main choice of learning media in the online learning process in class V of SDN 020 North Samarinda because WhatsApp made it easy for all groups to use, both teachers, students and parents of students. Through the WhatsApp Group, learning can also be carried out according to the RPP starting from the opening, core and closing activities. Then the features in the WhatsApp Group help the learning process such as chat features, voice notes, photos, videos and documents. The use of WhatsApp Groups in online learning has several obstacles, behind the existing barriers, teachers can minimize these obstacles.